2015
DOI: 10.4236/ojmi.2015.52008
|View full text |Cite
|
Sign up to set email alerts
|

Application of Magnetic Particle Imaging to Pulmonary Imaging Using Nebulized Magnetic Nanoparticles

Abstract: Purpose: To investigate the feasibility of applying magnetic particle imaging (MPI) to pulmonary imaging using nebulized magnetic nanoparticles (MNPs) and to quantify the mucociliary clearance in the lung, using small animal experiments. Materials and Methods: Intrapulmonary administration of MNPs was performed in seven-week-old male ICR (Institute of Cancer Research) mice (n = 8) using a nebulized microsprayer connected to a high-pressure syringe containing 50 μL of MNPs (500 mM Resovist®). We imaged the lung… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
4
1

Citation Types

0
38
0

Year Published

2016
2016
2023
2023

Publication Types

Select...
7
2

Relationship

1
8

Authors

Journals

citations
Cited by 39 publications
(38 citation statements)
references
References 22 publications
0
38
0
Order By: Relevance
“…This work on MPI lung perfusion adds to previous work on MPI preclinical imaging in the torso region, including on lung ventilation, whole body blood pool imaging and whole body stem cell tracking (showing 200 cell sensitivity) (Nishimoto et al 2015; Keselman et al 2016; Zheng, Vazin, et al 2015; Zheng, See, et al 2016). Collectively, the high quality images and range of applications demonstrated in the literature suggest the general utility of MPI for lung imaging.…”
Section: Discussionmentioning
confidence: 71%
See 1 more Smart Citation
“…This work on MPI lung perfusion adds to previous work on MPI preclinical imaging in the torso region, including on lung ventilation, whole body blood pool imaging and whole body stem cell tracking (showing 200 cell sensitivity) (Nishimoto et al 2015; Keselman et al 2016; Zheng, Vazin, et al 2015; Zheng, See, et al 2016). Collectively, the high quality images and range of applications demonstrated in the literature suggest the general utility of MPI for lung imaging.…”
Section: Discussionmentioning
confidence: 71%
“…Previously, Nishimoto (Nishimoto et al 2015) demonstrated promise for MPI in lung imaging with the first in vivo MPI ventilation studies in mice using a nebulized microsprayer to deliver Resovist to the lungs. Here, we report a method for preparing a novel MPI lung perfusion imaging agent, macroaggregated albumin-SPIOs (MAA-SPIOs), and demonstrate its efficacy and biodistribution for in vivo MPI lung perfusion imaging in rats.…”
Section: Introductionmentioning
confidence: 99%
“…MPI has been used in several in vivo application domains to date, including cell tracking (Zheng, Vazin, et al 2015; Zheng, See, et al 2016), cancer imaging (Yu et al 2016), blood pool and perfusion imaging (Orendorff et al 2016), angiography and cardiac imaging (J Weizenecker et al 2009), lung ventilation and perfusion studies (Nishimoto et al 2015; Zhou et al 2016), and predicting the effect of MFH (Kuboyabu et al 2016). These results highlight the strengths of MPI: zero background signal, zero depth attenuation of the signal, high sensitivity, linear quantification, and no half-life associated with the tracer signal such that physiologic clearance times determine the time horizons available in longitudinal studies.…”
Section: Introductionmentioning
confidence: 99%
“…MPI is best compared to gold-standard tracer imaging techniques, such as nuclear medicine, but without the limitations of radiation safety or radionuclide half-life for longitudinal imaging. As such, MPI shows excellent promise for clinical applications such as angiography (Haegele et al 2012; Salamon et al 2016), stem cell tracking and vitality assessment (Fidler et al 2015; Them et al 2016; Zheng, Vazin, et al 2015; Zheng, von See, et al 2016), brain perfusion (Orendorff et al 2016), lung perfusion (Zhou et al 2016),lung ventilation (Nishimoto et al 2015), cancer imaging (E. Yu et al 2016), and localized hyperthermia (Murase, Aoki, et al 2015; Hensley et al 2016).…”
Section: Introductionmentioning
confidence: 99%